Proposal of a probabilistic assessment of structural collapse concomitantly subject to earthquake and gas explosion - Abdollahzadeh, Gholamreza; Faghihmaleki, Hadi (Frontiers of Structural and Civil Engineering, 2018)
In recent decades, many public buildings, located in seismic-prone residential areas, had to grapple with abnormal loads against which the structures were unguarded. In this piece of research, an ordinary three dimensional reinforced concrete building is selected as case study. The building is located in an earthquake-prone region; however, it is designed according to seismic building codes. Yet, it is not shielded against abnormal loads, such as blasts. It is assumed that the building suffers a blast load, due to mechanical/thermal installation failure during or after intense seismic oscillations. These two critical incidents are regarded codependent and compatible. So the researchers developed scenarios and tried to assess different probabilities for each scenario and carried out an analysis to ensure if progressive collapse had set in or not. In the first step, two analysis models were used for each scenario; a non-linear dynamic time history analysis and a blast local dynamic analysis. In the second step, having the structural destructions of the first step in view, a pushdown analysis was carried out to determine the severity of progressive collapse and assess building robustness. Finally, the annual probability of structural collapse under simultaneous earthquake and blast loads was estimated and offered.